Just for the cameras [large type] - Quinn, Meghan (Bay Area players, 2026)
"They're faking it for the cameras. But what if the sparks are real? Graydon St. John doesn't do drama-or public appearances. The brooding defensive end for the San Francisco Foghorns prefers silence, solitude, and avoiding headlines. But when a league-wide PR scandal forces him into a media stunt at the city zoo, he's suddenly face-to-face with squawking birds, nosy fans, and the zookeeper who seems to hate his guts on sight. Maple Baker loves her flamingos. Loud, pink, messy? Sure. But they're hers. And the last thing she needs is a grumpy football player stomping into her sanctuary with a bad attitude and a bigger ego. Unfortunately, they've been paired for the zoo's new public outreach program, and the cameras are already rolling. The banter is sharp. The tension is electric. And the more they pretend to play nice for the press, the more their fake flirtation starts to feel like something dangerously real. But when family secrets, viral fame, and a PR romance gone off-script threaten everything Maple's worked for, Graydon must decide if he's willing to fight for love-or let it slip away to protect her."--